The cosmological behavior of Bekenstein's modified theory of gravity - Bourliot, F; Ferreira, P; Mota, D; Skordis, C (2006)
We study the background cosmology governed by the Tensor-Vector-Scalar theory of gravity proposed by Bekenstein. We consider a broad family of potentials that lead to modified gravity and calculate the evolution of the field variables both numerically and analytically. We find a range of possible behaviors, from scaling to the late time domination of either the additional gravitational degrees of freedom or the background fluid.